ANALISIS RISIKO DAN PENGARUHNYA TERHADAP PELAKSANAAN PROYEK KONSTRUKSI PERUMAHAN GRIYA PESONA INDAH DI KOTA KEDIRI (Jurnal Spesialis Teknik Sipil (JSpTS), 2022)
A housing development project is a project with certain resources and a certain time limit to obtain construction results. However, in practice there are certain risks. Therefore, good risk management is needed to get the desired results. The purpose of this study is to identify risks in the construction of the GRIYA PESONAN INDAH Housing Project and how to respond to risks. Identify risk by using the Risk Breakdown Structure (RBS). Classification of risk between impact and intensity using the Pobability impact matrix. Furthermore, risk analysis uses the Analytical Network Process (ANP). ANP is appropriate to be applied to decision making that faces interrelated factors and systematic feedback. Through RBS can be shown 6 risk groups with 24 risk items. With expert respondents, ANP results show that the most dominant risk group among other risk groups is the risk of the construction process. Meanwhile, among the 24 risk items, the risk of coordination and poor performance is the most dominant risk. Furthermore, from the experts obtained recommendations for solutions to the dominant risk, namely by providing training, tightening evaluation.